Local Content and Local Participation in the Ghanaian Mining Industry : The Challenges, Prospects and the Wayforward - Kuveya, Lloyd (University of Pretoria, 2024)
Mini Dissertation (MPhil (Extractive Industry Policy, Management and Regulation))--University of Pretoria, 2023.